2014
DOI: 10.2478/intox-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, mechanism and health effects of some heavy metals

Abstract: Heavy metal toxicity has proven to be a major threat and there are several health risks associated with it. The toxic effects of these metals, even though they do not have any biological role, remain present in some or the other form harmful for the human body and its proper functioning. They sometimes act as a pseudo element of the body while at certain times they may even interfere with metabolic processes. Few metals, such as aluminium, can be removed through elimination activities, while some metals get ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
2,118
0
76

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 4,683 publications
(2,568 citation statements)
references
References 59 publications
21
2,118
0
76
Order By: Relevance
“…At higher doses, heavy metals can cause irreversible brain damage (Jaishankar et al, 2014). It is also very important to consider that children receive higher doses of metals from food than adults, as they consume more food in relation to their BW (Thirulogachandar et al, 2014).…”
Section: Heavy Metals and Human Healthmentioning
confidence: 99%
“…At higher doses, heavy metals can cause irreversible brain damage (Jaishankar et al, 2014). It is also very important to consider that children receive higher doses of metals from food than adults, as they consume more food in relation to their BW (Thirulogachandar et al, 2014).…”
Section: Heavy Metals and Human Healthmentioning
confidence: 99%
“…Besides the fact that antioxidant systems composed of antioxidants and specific enzymes, are being studied extensively, still some important intrinsic mechanisms and characteristics about this network remain unknown (47)(48)(49)(50). The stress that heavy metals have on antioxidant system and plant cell is presented on Fig.…”
Section: Effects Of Heavy Metals On Antioxidant Activity In Plantsmentioning
confidence: 99%
“…Heavy metal toxicity can lower energy levels and damage the functioning of the brain, lungs, heart, blood vessels, kidney, liver, blood composition and other important organs. Repeated long-term exposure of some metals and their compounds may even cause cancer [5].…”
Section: The Role Of Heavy Metalsmentioning
confidence: 99%
“…In vivo and in vitro studies have shown that chronic lead exposure causes HTN and cardiovascular disease by promoting oxidative stress, limiting nitric oxide availability, impairing nitric oxide signalling, augmenting adrenergic activity, increasing endothelin production, altering the renin-angiotensin system, raising vasoconstrictor prostaglandins, lowering vasodilator prostaglandins, promoting inflammation, disturbing vascular smooth muscle Ca(2+) signalling, diminishing endotheliumdependent vasorelaxation, and modifying the vascular response to vasoactive agonists [5]. Moreover, lead has been shown to cause endothelial injury, impede endothelial repair, inhibit angiogenesis, reduce endothelial cell growth, suppress proteoglycan production, stimulate vascular smooth muscle cell proliferation and phenotypic transformation, reduce tissue plasminogen activator, and raise plasminogen activator inhibitor-1 production [6][7][8][9].…”
Section: The Role Of Heavy Metalsmentioning
confidence: 99%